98.3k views
2 votes
What is the solution set of 2x(x - 1) = 3?

1 Answer

3 votes

First you must distribute the 2x to the numbers inside the parentheses

(2x * x) + (2x * -1) = 3


2x^(2) - 2x = 3

To make this a quadratic equation you can solve bring the 3 over to the left side of the equation by subtracting it to both sides


2x^(2) - 2x - 3 = 0

Use the quadratic equation to solve this (image of the quadratic equation is below)

Remember that quadratic functions are set up like so:


ax^(2) +bx +c = 0

That means that in this equation...

a = 2

b = -2

c = -3

^^^Plug these numbers into the quadratic equation and solve...


\frac{2+/-\sqrt{(-2)^(2)-4(2)(-3)}}{2(2)}


(2 +/-√(4+24))/(4)


(2+/-√(28) )/(4)


(2+/-2√(7) )/(4)


(1+/-√(7) )/(2)

Keep in mind that +/- is ±


(1+√(7) )/(2)


(1-√(7) )/(2)

^^^Exact answers

Approximations:

1.823

-0.823

Hope this helped!

~Just a girl in love with Shawn Mendes

What is the solution set of 2x(x - 1) = 3?-example-1
User Som
by
4.9k points